2004
DOI: 10.1007/s00442-004-1730-0
|View full text |Cite
|
Sign up to set email alerts
|

The persistence of ripe fleshy fruits in the presence and absence of frugivores

Abstract: A trade-off between antimicrobial defences and palatability to dispersers may place limits on fruit persistence in nature. The retention times of ripe fruits on 34 wild plant species under natural conditions (unbagged persistence) and when fruits had been bagged with nylon mesh to exclude frugivores (bagged persistence) were compared in Hong Kong, China (22 degrees N). Bagged persistence is a measure of the effectiveness of fruit defence while unbagged persistence is an inverse measure of attractiveness to ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…However, fruit consumption by antagonists was not measured in this study and other similar studies on limited numbers of fruit species (Cipollini and Stiles 1993;Cipollini and Levey 1997a). Even though, Tang et al (2005) also excluded seed dispersers from fruits and explained the variation in persistence time of these fruits with variation in defense against pathogens, they did not measure the amount of secondary compounds, and therefore the predictions of the models on fruit biochemistry could not be directly tested.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 58%
See 2 more Smart Citations
“…However, fruit consumption by antagonists was not measured in this study and other similar studies on limited numbers of fruit species (Cipollini and Stiles 1993;Cipollini and Levey 1997a). Even though, Tang et al (2005) also excluded seed dispersers from fruits and explained the variation in persistence time of these fruits with variation in defense against pathogens, they did not measure the amount of secondary compounds, and therefore the predictions of the models on fruit biochemistry could not be directly tested.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 58%
“…We excluded the second and third morphological PCs because we were particularly interested in the eVects of chemical variables based on our study questions. Moreover, previous studies reported that chemical characters are more important than morphological ones (Schaefer et al 2003;Tang et al 2005) and the Wrst morphological PC accounts for most of morphological variance allowing us to correct for fruit morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no data on the defensive chemistry of other Hong Kong fruits, but Tang et al (2005) There have been no other local reports of seeds with undeveloped embryos in mature fruits, but I. hanceana, the only Ilex tested, was one of only eight tree species (of 40 tested) to retain viable seeds after being buried for 2 years in the forest (Zhuang and Corlett 1999).…”
Section: Ilex In the Tropicsmentioning
confidence: 95%
“…A variety of evidence suggests that fruit chemistry reflects an adaptive balance between attracting dispersers and deterring pests and pathogens (Cipollini et al 2004;Tang et al 2005). There is also evidence that frugivores can detect small differences in fruit quality (e.g., Schaefer et al 2003a) and that ranking of fruit preferences is fairly consistent across sites and time (Herrera 1998;Carlo et al 2003).…”
Section: Comparisons Among Speciesmentioning
confidence: 97%